Disability, gender and state policy : exploring margins - Nilika,Mehrotra (Rawat Publications, 2013)
Foregrounding disability from an anthropological perspective, this book contributes to the studies in marginalization and social inequalities in India. Tracing global debates on the definition of disability, rehabilitation, and policies, it focuses on a South Asian model of disability. Covering a wide range of issues from international and national contexts, the book critically examines the role of disability rights movements, as well as the regional policies and practices. Disability, Gender & State Policy explores the cultural perceptions of disability, the construction of gender and personhood in rural and urban contexts, and the issues in social support and care work. It also highlights the implications of globalization and psycho-social disabilities among poor urban women. The book analyzes disabled persons' access to resources like education and employment opportunities in diverse sectors, providing a comprehensive account of the disabled, embedded in India's communities, citizenry, and democracy